(untitled) (Journal of the Bangladesh Agricultural University, 2012)
An investigation was carried out on fish landing centers, fish markets and fish fauna of the Mymensingh town to overview the location of the fish landing/entering centers, the source of supply and availability of fisheries organisms in Mymensingh town. The investigation was conducted from October 2009 to September 2010 in sixteen landing centers and markets of Mymensingh town. Among a total of 122 species of fishes were available of which, 113 were finfish and 9 were shellfish. Out of 113 finfish, 85 were freshwater fish species, 14 were exotic species, 14 were marine species, 7 were prawn /shrimps and 2 were mud crab and tortoise. Different types of freshwater fish, marine fish, crustacean and dry fish were found in Mymensingh town. The most abundant freshwater fish species were Catla catla, Labeo rohita, Clarias batrachus, Cirrhinus cirrhosus, Channa punctatus. Among the marine fishes Lates calcarifer, Euthynnus affinis and Mugil cephalus were recorded. The shellfishes, Macrobrachium rosenbergii and Penaeus monodon were most abundant. Significant amount of carps were imported from inside and outside of the districts. Besides the carps, small quantities of other fish, e.g, hilsha, catfish, tilapia, small indigenous fish, prawn and shrimp and other fish including marine can be seen in the fish landing centers and fish markets in Mymensingh town. Trains, buses, trucks and pickups were used as transport of fish to the landing centers from outside of Mymensingh town. Virtually most of the fish (84.6 %) were brought from different areas of the district and adjacent district like Netrokona, Jamalpur, Gazipur and Kishoreganj. The rest (15.4 %) were brought from external source in Mechhua bazar, Natun bazar, Sankipara bazar, Charpara bazar and Kathgola bazar. Main source of the fishes were different ponds, haors, beels and rivers of Mymensingh and adjacent districts. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11046 ]J. Bangladesh Agril. Univ. 9(2): 311318, 2011